Different Forms of AMPA Receptor Mediated LTP and Their Correlation to the Spatial Working Memory Formation - Shimshek, Derya R.; Bus, Thorsten; Schupp, Bettina; Jensen, Vidar; Marx, Verena; Layer, Liliana E.; Köhr, Georg; Sprengel, Rolf (Frontiers in Molecular Neuroscience, 2017)
Spatial working memory (SWM) and the classical, tetanus-induced long-term potentiation (LTP) at hippocampal CA3/CA1 synapses are dependent on L-α-amino-3-hydroxy-5-methylisoxazole-4-propionate receptors (AMPARs) containing GluA1 subunits as demonstrated by knockout mice lacking GluA1. In GluA1 knockout mice LTP and SWM deficits could be partially recovered by transgenic re-installation of full-length GluA1 in principle forebrain neurons. Here we partially restored hippocampal LTP in GluA1-deficient mice by forebrain-specific depletion of the GluA2 gene, by the activation of a hypomorphic GluA2(Q) allele and by transgenic expression of PDZ-site truncated GFP-GluA1(TG). In none of these three mouse lines, the partial LTP recovery improved the SWM performance of GluA1-deficient mice suggesting a specific function of intact GluA1/2 receptors and the GluA1 intracellular carboxyl-terminus in SWM and its associated behavior.